PHYSICAL-CHEMICAL CHARACTERIZATION AND ANTIOXIDANT CAPACITY OF THE AQUEOUS EXTRACT OF THE FRUITS OF CAESALPINIA SPINOSA (MOLINA) KUNTZE “TARA” - Limaymanta Gonzales, Jimmy (2023)
Caesalpinia spinosa (Molina) Kuntze is a plant species with great potential in medicine, mining, etc. The objectives were to determine the physicochemical parameters and the in vitro antioxidant capacity of the aqueous extract of the fruits of Caesalpinia spinosa (Molina) Kuntze. In the aqueous extract, the physical-chemical characteristics and the presence of main groups of metabolites were determined through phytochemical screening, associated with biological activity. The content of total polyphenols was determined by the Folin-Ciocalteu method and the antioxidant capacity was evaluated in vitro by the method of DPPH and the method of ABTS. The aqueous extract of Caesalpinia spinosa (Molina) Kuntze had a relative density of 1,0024 g/mL. Regarding the phytochemical screening, some metabolites were identified, highlighting phenolic compounds, flavonoids, tannins and heterosides. The total phenolic content was 365,75 (μg EAG/mg). The antioxidant capacity with the DPPH method was IC50 3,38 μg/mL and with the ABTS method IC50 4,51 μg/mL. The trolox equivalent antioxidant capacity (TEAC-DPPH) was 2,19 (μg trolox/mg) and the trolox equivalent antioxidant capacity (TEAC-ABTS) was 2,14 (μg trolox/mg). It is concluded that the aqueous extract of Caesalpinia spinosa (Molina) Kuntze